2019
DOI: 10.1038/s41598-019-48499-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of surface glycans of extracellular vesicles on cellular uptake

Abstract: Extracellular vesicles (EVs) are important mediators of cell-cell communication in a broad variety of physiological contexts. However, there is ambiguity around the fundamental mechanisms by which these effects are transduced, particularly in relation to their uptake by recipient cells. Multiple modes of cellular entry have been suggested and we have further explored the role of glycans as potential determinants of uptake, using EVs from the murine hepatic cell lines AML12 and MLP29 as independent yet comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 58 publications
3
136
0
Order By: Relevance
“…Liang et al provided strong evidence that N-linked glycosylation directs glycoprotein sorting into sEVs [38], while Royo et al reported that the modification of the glycosylated complexes on the EV surface could alter the biodistribution of these sEVs in mice [39]. More recently, Williams and colleagues showed that N-glycosylation is related to decrease of sEVs cellular uptake [28]. We confirmed these findings by treating sEVs with N-glycosidase F which promoted cellular uptake of sEVs in recipient cells (Figure 9c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liang et al provided strong evidence that N-linked glycosylation directs glycoprotein sorting into sEVs [38], while Royo et al reported that the modification of the glycosylated complexes on the EV surface could alter the biodistribution of these sEVs in mice [39]. More recently, Williams and colleagues showed that N-glycosylation is related to decrease of sEVs cellular uptake [28]. We confirmed these findings by treating sEVs with N-glycosidase F which promoted cellular uptake of sEVs in recipient cells (Figure 9c).…”
Section: Discussionmentioning
confidence: 99%
“…We observed and confirmed an increased uptake when sEVs were pre-treated with anti-CD147 antibodies as well as when recipient cells were treated with specific anti-CD147 siRNA (Figure 9b). Recently, it has been shown that N-glycans are key players in the tuning of sEVs uptake [28]. CD147 is an N-glycosylated protein so we hypothesized that this post-translational modification may be involved in sEVs cellular uptake.…”
Section: Cd147 Mediates Sev-effects In Recipient Cellsmentioning
confidence: 99%
“…Glycosylation is at the base of many biological functions of EVs, such as cargo protein recruitment and cellular recognition and uptake [ 107 , 108 ]. Alterations in the glycosylation pattern has been associated with different pathologies, for example, cancer, and these changes are closely correlated with the specific malignant transformation and progression.…”
Section: Engineered Evsmentioning
confidence: 99%
“…It is well known that glycosylation has an important role in different biological function of EVs, like in the cargo proteins recruitment [61] and in the cellular recognition and uptake [62]. Recent glycomic analyses [63], performed by lectin microarray technology on EVs derived from different biological sources, reveal both enrichment and exclusion of glycan epitopes with respect to the membranes of their parental cells.…”
Section: Chemico-physical Functionalizationmentioning
confidence: 99%